Prevalence of Mental Health Complaints Among Performing Arts Students Is Associated With COVID-19 Preventive Measures - Stubbe, Janine H.; Tiemens, Annemiek; Keizer-Hulsebosch, Stephanie C.; Steemers, Suze; van Winden, Diana; Buiten, Maurice; Richardson, Angelo; van Rijn, Rogier M. (Frontiers in Psychology, 2021)
The aim of this study was to investigate the effect of COVID-19 preventive measures on the mental health of performing arts students. In a prospective cohort study, performing arts students (N = 213) from Codarts Rotterdam, University of the Arts, were invited to monitor their health during one academic year (September 2019 – May 2020). Every month, students completed items on mental health complaints, stress, and sleep quality. Chi-square tests and repeated-measures ANOVA with deviation contrasts were performed to investigate whether COVID-19 preventive measures were associated with changes in mental health complaints, stress scores, and sleep quality. During the COVID-19 lockdown, subjective mental health, Mental Health Inventory-5 (MHI-5), and items on loneliness were additionally completed by the respondents. A total of 98 students (46.0%) were included in the analyses. The three-month prevalence of mental health complaints was significantly higher during the COVID-19 lockdown compared to the two pre-COVID-19 periods (p < 0.001). Mean stress scores were significantly lower for February (35.20) and March (36.41) when compared to the overall mean (40.38). Sleep quality scores (mean) were significantly higher for April (6.90), and May (6.89) when compared to overall mean (6.58). Furthermore, at least 75.5% of the participants dealt with moderate to very severe loneliness in all three months during the COVID-19 lockdown. During lockdown, performing arts students perceived less stress and their sleep quality increased. However, the prevalence of mental health complaints increased. Besides, 3 out 4 students dealt with moderate to very severe loneliness.